Scientific Attitude of Prospective Science Teachers in Indonesia: A Psychometric Evaluation - Tania, Lisa; Saputra, Andrian (FKIP Universitas Lampung, 2022)
The purpose of this study was to evaluate the scientific attitude of prospective science teacher students as well as to validate the scientific attitude assessment instrument that had been developed (Moore & Foy, 1997). This research procedure includes adapting the instrument, analyzing the content validity, delivering the instrument to sample and evaluating the research data. The data obtained were analyzed statistically using factor analysis techniques to determine the contribution of each item, analysis the reliablity and Pearson product moment correlation. The research sample was 525 prospective science teachers who were taken by using random technique at University of Lampung. The results showed that scientific attitude consisted of 4 main factors, namely science is about understanding, explaining, and aiming to help other people's lives better (factor 1), I want to become a scientist (factor 2), the task of a scientist (factor 3), and science is rigid (factor 4). Furthermore, factor 3 and factor 1 as the dominant scientific attitude possessed by students, followed by factor 2 and factor 4. The scientific attitude was dominated by the understanding that science is about understanding and explaining scientific facts and the obligations of a scientist. . But they themselves do not really want to be a scientist. The structural model was declared valid, and according to the model fit index criteria, χ2 / df, GFI, AGFI, RMR, RMSEA, CFI, NFI, dan IFI with successive values of 1.331/(p < 0.05); 0.981; 0.968; 0.022; 0.025; 0.91, 0.988; 0.954; 0.937. Keywords: scientific attitude, academic achievement, factor analysis DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp419-427